Quality of refrigerated raw milk obtained in production units in southwest Paraná (Revista de Ciências Agroveterinárias, 2017)
The quality of milk is one of the most widely discussed topics in the national dairy production scenario. Thus, the objective of this study was to evaluate the qualitative parameters and provide information regarding the factors that can affect the quality of refrigerated raw milk obtained monthly in 40 production units in six municipalities in Paraná Southwest region. Data collection was carried out of the properties with the aid of a semi-structured questionnaire. Twelve parameters were considered inherent in dairy farming and that can influence the quality of the raw material, as follows: production stratum, production systems, milking, cooling, labor, and service, frequency of care, hygiene of cooler, the milking teat disinfection ceilings and structure of the milking environment. The milk samples were analyzed for their composition of: fat, protein, lactose and Dry Total Extract (DTE), the Somatic Cell Count (SCC) and Count Standard on plates (CSP). The protein and SCC were not influenced by any of the parameters studied. The fat content is one of the milk components most likely to introduce variation in the ratio, which was influenced by the production stratum, type of labor, frequency of service, cooler cleaning and type of containment available on the property. The variables that showed higher values for fat and CSP are associated with properties with technological level and lower production. Nutritional aspects that promote increased production, as identified in the higher milk production systems result in lower percentage of milk fat. Facilities that have channeled milking and cooling by expansion provide better results for CSP. Practices such as the use of pre and post-dipping, cooler cleaning and milking machine with hot water and detergent significantly reduce the CSP.
Keywords: somatic cells; chemical physical composition; fat; milk production; protein; Instruction 62; microorganisms.